Persoalan Struktural dalam Politik Penegakan Hukum Sumber Daya Alam dan Lingkungan Hidup - Nagara, Grahat; Amri, Belinda Sahadati; Patria, Dian; Andhika, Farid (Komisi Pemberantasan Korupsi, 2019)
Structural problems cause law enforcement in the field of natural resources and the environment to be powerless when dealing with the exploitation of unregistered natural resources, damage to the environment due to lack of compliance, and corruption in the joints of government administration in the field of resources natural. Even though the natural resources sector is a sector that has adequate instruments of law enforcement, in practice law enforcement against perpetrators of crimes in the field of natural resources is not very effective. This paper will elaborate on this obstacle, and also describe the experience and learning of the Corruption Eradication Commission to strengthen law enforcement in the field of natural resources through the initiatives that are underway in the National Movement to Save Natural Resources. Specifically by not only being a trigger (trigger mechanism) for the process of law enforcement, the National Movement to Save Natural Resources also encourages the strengthening of legal politics in law enforcement in the field of natural resources-environment.